STRUCTURAL MANIFESTATIONS OF ER-STRESS IN THE NEPHRON HAEMOCAPILLARY ENDOTHELYCYTES IN EXPERIMENTAL BURN DISEASE IN RATS - Lakhtadyr, T.V.; Cherkasov, E.V.; Yaremenko, L.M.; Grabovoy, A.N.; Shepitko, K.V. (World of Medicine and Biology, 2020)
Studies on structural manifestations of ER-stress, apoptosis and necrosis in endothelial cells of nephron hemocapillaries in experimental burn disease in rats (caused by burn injury of the skin with an area of 21-23% of the body surface) have shown indisputable protector and therapeutic advantages of intravenous colloidal hyperosmolar solutions infusion over the isotonic solution infusion, which was 0.9% NaCl solution. The most vulnerable organelle in endothelial cells of nephron hemocapillaries in experimental burn disease and in detoxification therapy performed is a granular endoplasmic reticulum, therefore an important evidence of the used detoxification solutions efficacy is the nature of the ER-stress course. Under the conditions of intravenous colloidal hyperosmolar solutions infusion (lactoprotein with sorbitol and HAES-LX-5%), normalization of ER stress is observed, accompanied by apoptotic changes of endothelial cells, but it is not accompanied by necrosis of endothelial cells. The consequence of the endothelial cells necrosis in the kidney hemocapillaries is the formation of paravasal hemorrhages and lympho-leukocyte infiltrates, which is evidence of impaired filtration and reabsorption functions of the kidneys, as well as of the inflammatory process progress in the kidneys.